Molecular interference for surface sites as a hidden driver of coagulation impairment in wastewater-impacted drinking water production - Mengjie Liu; Baofeng Zhu; Nigel J.D. Graham; Wenzheng Yu (Water Research, 2026)

Agricultural Phosphorus Pollution Leads to a Two-Stage Release of Organic Matter in Sediments at the Bottom of Lake - Hankun Yang; Yun Xiao; Xingshe Zhu; Nigel J.D. Graham; Wenzheng Yu (Water Research, 2026)

Nexus between environmental aging, ecological risks, and removal strategies for micro- and nano-plastics in aquatic systems - Fan Lu; Tao Yang; Jianbo Zhao; Di Cai; Marcelo A. Nolasco; Shikun Cheng; Nigel J.D. Graham; Zhen Yang (Chemical Engineering Journal, 2026)

Enhanced removal of pharmaceuticals in a 3D electrochemical reactor with scalable-produced tri-functional cyanobacterial-bloom-waste-derived single-Fe-atom particle electrodes - Jinhui Zhang; Xin Jiang; Zhen Yang; Shikun Cheng; Zhiling Guo; Marcelo A. Nolasco; Ramiro G. Etchepare; Bo Bian; Jieshu Qian; Zifu Li; Nigel J.D. Graham; Iseult Lynch (Chemical Engineering Journal, 2026)

Coagulation mechanisms of ferric chloride and polyaluminum ferric chloride (PAFC) under high-concentration NaCl/Na2SO4 conditions - Xingshe Zhu; Qingwei Li; Hankun Yang; Siyi Liang; Nigel J.D. Graham; Wenzheng Yu (Journal of Environmental Sciences, 2026)

Optimizing anaerobic Co-digestion of antibiotic fermentation residue and sludge with iron nanoparticles: Impacts on methane production, microbial dynamics, and biocompatibility - Qianqian Zhang; Yu Yang; Li-an Hou; Nigel J. D. Graham; Yaobin Zhang; How Yong Ng (ENGINEERING Environment, 2026)

Bimetallic catalytic ceramic membrane for sustained water purification: Role of Cu in stabilizing reduced Co centers - Jiaqi Yang; Kexuan Gao; Yiran Chai; Nigel J.D. Graham; Li-an Hou; Yu Yang (Chemical Engineering Journal, 2026)

Impacts of lignin nanoparticles as antibacterial agents on the composition of biofilms in water treatment - Jiesi Zhang; Yufei Li; Nigel Graham; Minmin Liu; Wenzheng Yu (Water Research, 2026)

Amoeba-inspired nano-robots for trace low-molecular-weight emerging contaminant removal from water - Lina Zhao; Shikun Cheng; Suwan Xing; Ahmed M. Elgarahy; Khalid Z. Elwakeel; Zhen Yang; Zhiling Guo; Zifu Li; Nigel J.D. Graham; Iseult Lynch (Water Research, 2026)

A comprehensive review of global per- and polyfluoroalkyl substances (PFAS) in water and their remediation through degradation and defluorination techniques - Mian Jawaduddin; Zhaoyang Su; Sajid Rashid; Nigel Graham; Wenzheng Yu (Chemical Engineering Journal, 2026)

Enhancing floc growth by oxidative and reductive modification of organic matter structure - Baofeng Zhu; Mengjie Liu; Kai Zhang; Nigel Graham; Wenzheng Yu (Water Research, 2026)

PFAS-driven modulation of algal organic matter enhances dissolved organic matter reactivity and disinfection by-product formation: Mechanistic elucidation via multi-spectroscopic analysis, and mitigation by coagulation and nanofiltration - Mian Jawaduddin; Zhaoyang Su; Sajid Rashid; Muhammad Saboor Siddique; Nigel Graham; Wenzheng Yu (Journal of Hazardous Materials, 2026)

Inclusion of nanofiltration as a robust barrier against municipal effluent impacts in drinking water treatment - Mengjie Liu; Baofeng Zhu; Chunjiang Wu; Nigel J.D. Graham; Wenzheng Yu (Water Research, 2026)

Collaborative catalysis of single atoms and atomic clusters as dual sites for confined peroxymonosulfate activation to coordinate radical and singlet oxygen pathways - Mengdi Zhao; Zibo Xu; Xiaoguang Duan; Nigel J.D. Graham; Hua Zhong; Daniel C.W. Tsang (Water Research, 2026)

The influence of hydroxylamine on Fe coagulation when treating NOM and TC from real-world waters - Qingyun Song; Bingqian Yang; Kai Zhang; Nigel Graham; Wenzheng Yu (Journal of Environmental Chemical Engineering, 2025)

Role of granular activated carbon's physical properties and surface chemistry in sustaining biological activated carbon performance - Han Chen; Junling Wang; Lei Xu; Peng Zhou; Nigel J.D. Graham; Wenzheng Yu (Chemical Engineering Journal, 2025)

Reduced Cytochrome c: Exploring Its Promoting Function in Synergistic Denitrification by Pseudomonas sp. JM-7 and Thiobacillus denitrificans - Bobo Xing; Ji Li; Linlin Li; Nigel J.D. Graham; Xian Li; Wenzheng Yu (Water Research, 2025)

Overlooked influence of phosphate on the performance of a dual membrane process with coagulation pretreatment - Cong Ma; Zixiang Zhang; Lei Xu; Sajid Rashid; Guibai Li; Nigel Graham; Wenzheng Yu (Water Research, 2025)

Constructing S/N-vacancy-and Co/Mo-bimetallic-catalysts for tetracycline degradation through peroxymonosulfate activation: evolution of active substance - Jiaqi Yang; Yu Yang; Kexuan Gao; Nigel J.D. Graham; Li-an Hou (Environmental Research, 2025)

Nanoconfined GO/MXene membranes decorated with sea urchin-like cobalt catalyst toward peroxymonosulfate activation to generate singlet oxygen with high selectivity for enhanced Fenton-like reactions - Lijia Wang; Wenwa Weng; Nigel Graham; Wenzheng Yu; Kening Sun; Ting Liu (Chemical Engineering Journal, 2025)

Deciphering membrane biofouling induced by micro-/nano-plastics in nanofiltration: Metagenomic insights and spacer-driven mitigations - Xinhui Liu; Yu Yang; Nigel J D Graham; Satoshi Takizawa; How Yong Ng (Water Research, 2025)

The nanoscale explanation of metal cations differences in enhancing the Fe(III) coagulation performance - Bingqian Yang; Peng Zhou; Long Tian; Nigel Graham; Guibai Li; Zhaoyang Su; Wenzheng Yu (Water Research, 2025)

Enhanced methane production and biofouling mitigation by Fe2O3 nanoparticle-biochar composites in anaerobic membrane bioreactors - Qianqian Zhang; Yu Yang; Chung-Hak LEE; Nigel J.D. Graham; How Yong Ng (Water Research, 2025)

Carbon-mineral composite design for microwave-assisted degradation of organic contaminants - Qingyi Liliu; Zibo Xu; Yuqing Sun; Eakalak Khan; Nigel J.D. Graham; Daniel C.W. Tsang (Journal of Environmental Management, 2025)

Understanding the risk of enhanced particle penetration into slow sand filter beds when using underwater skimming techniques - Tolulope Elemo; Michael Chipps; Nigel Graham; Andrew Turner; Bruce Jefferson; Francis Hassard (Journal of Environmental Management, 2025)

Evaluating the impact of underwater skimming on slow sand filter performance and operation - Tolulope Elemo; Michael Chipps; Nigel Graham; Andrew Turner; Sophie Bretagne; Bruce Jefferson; Francis Hassard (Water Research, 2025)

The irreversible transformation of the molecular structure of humic acid during pH change and its effects on the formation of disinfection by-products - Yun Xiao; Yufei Li; Hankun Yang; Sajid Rashid; Nigel Graham; Wenzheng Yu (Journal of Hazardous Materials, 2025)

Effect of seasonal variation of natural organic matter on the fouling of hydrophilic ultrafiltration membranes - Huimin Zhou; Ting Liu; Nigel Graham; Kening Sun; Sylwia Mozia; Wenzheng Yu (Journal of Water Process Engineering, 2025)

Predicting the impact of underwater skimming on dissolved oxygen consumption in slow sand filters for potable water treatment - Tolulope Elemo; Michael Chipps; Nigel Graham; Andrew Turner; Bruce Jefferson; Francis Hassard (Science of The Total Environment, 2024)

Per- and polyfluoroalkyl substances (PFAS) at low concentration improve coagulation efficiency but induce higher membrane fouling in drinking water treatment - Qianyi Chen; Junling Wang; Zhaoyang Su; Long Tian; Fan Huang; Ting Liu; Nigel Graham; Guibai Li; Wenzheng Yu (Environmental Pollution, 2024)

Removal of refractory humic acid-like components from UF filtrate of landfill leachate through pH adjustment and coupled electrochemical process - Jinjin Zhao; Kai Zhang; Nigel J.D. Graham; Wenzheng Yu (Chemical Engineering Journal, 2024)

Exploring the influence of aquatic phosphate on Fe floc dynamics in water treatment - Lei Xu; Zixiang Zhang; Nigel J.D. Graham; Wenzheng Yu (Water Research, 2024)

Capabilities of Microbial Consortia from Disparate Environment Matrices in the Decomposition of Nature Organic Matter by Biofiltration - Fan Huang; Nigel J.D. Graham; Zhaoyang Su; Lei Xu; Wenzheng Yu (Water Research, 2024)

Fouling behavior of BTEX in petrochemical wastewater treated by nanofiltration (NF) - Kexuan Gao; Yu Yang; Ao Li; Jian Pu; Satoshi Takizawa; Nigel J.D. Graham; Li-an Hou (Journal of Hazardous Materials, 2024)

Self-assembled membrane with excellent antifouling performance for enhanced treatment of petrochemical wastewater - Kexuan Gao; Yu Yang; Nigel J.D. Graham; Ying Zhang; Yilin Jiang; Cheng Duan; Ao Li; Qianqian Zhang; Xiaoqiang An; Li-an Hou (Chemical Engineering Journal, 2024)

Pulsed electro-catalysis enables effective conversion of low-concentration nitrate to ammonia over Cu2O@Pd tandem catalyst - Fei Dou; Fengchen Guo; Bo Li; Kai Zhang; Nigel Graham; Wenzheng Yu (Journal of Hazardous Materials, 2024)

The application of chitosan quaternary ammonium salt to replace polymeric aluminum ferric chloride for sewage sludge dewatering - Minmin Liu; Sajid Rashid; Wei Wang; Huihui Zhang; Yawei Zhao; Xingmin Fu; Zhaoyang Su; Nigel Graham; Wenzheng Yu (Water Research, 2024)

Bioinspired stormwater control measure for the enhanced removal of truly dissolved polycyclic aromatic hydrocarbons and heavy metals from urban runoff - Lina Zhao; Tao Lei; Ruhui Chen; Ziqi Tian; Bo Bian; Nigel J.D. Graham; Zhen Yang (Water Research, 2024)

Uncovering the neglected role of anions in trivalent cation-based coagulation processes - Mengjie Liu; Xun Liu; Nigel J.D. Graham; Wenzheng Yu (Water Research, 2024)

The influence of molecular weight of adsorbed natural organic matter on the removal of dissolved black carbon by coagulation - Minmin Liu; Qingxuan Lu; Nigel Graham; Wenzheng Yu (Chemical Engineering Journal, 2024)

Promoting denitrification via high electron conversion ratio in the iron valence Cycle: Prospects for Pseudomonas sp. JM-7 application in environmental engineering - Bobo Xing; Ji Li; Linlin Li; Nigel J.D. Graham; Binghao Zhao; Xian Li; Wenzheng Yu (Chemical Engineering Journal, 2024)

New insights into the concentration-dependent regulation of membrane biofouling formation via continuous nanoplastics stimulation - Xinhui Liu; Yu Yang; Satoshi Takizawa; Nigel J.D. Graham; Chao Chen; Jian Pu; How Yong Ng (Water Research, 2024)

Simultaneous removal of NOM and sulfate in a bioelectrochemical integrated biofilter treating reclaimed water - Lei Xu; Shian Song; Nigel J.D. Graham; Wenzheng Yu (Water Research, 2024)

A comprehensive evaluation of the temporal and spatial fouling characteristics of RO membranes in a full-scale seawater desalination plant - Chao Chen; Yu Yang; Nigel J.D. Graham; Zhenyu Li; Xingtao Yang; Zhining Wang; Nadia Farhat; Johannes S. Vrouwenvelder; Li-an Hou (Water Research, 2024)

Direct generation of DBPs from city dust during chlorine-based disinfection - Lei Xu; Shian Song; Nigel J D Graham; Wenzheng Yu (Water Research, 2024)

In-depth study of the removal of Mn(II) by Fe(VI) treatment and the profound influence of NOM on floc formation and properties - Bingqian Yang; Sajid Rashid; Nigel Graham; Guibai Li; Wenzheng Yu (Water Research, 2023)

Floc aging: Crystallization and improving low molecular weight organic removal in re-coagulation - Qingyun Song; Bingqian Yang; Mengjie Liu; Shian Song; Nigel Graham; Wenzheng Yu (Water Research, 2023)

FexO/FeNC modified activated carbon packing media for biological slow filtration to enhance the removal of dissolved organic matter in reused water - Hankun Yang; Lei Xu; Yujuan Li; Hongyu Liu; Xue Wu; Peng Zhou; Nigel J.D. Graham; Wenzheng Yu (Journal of Hazardous Materials, 2023)

An overlooked crystallization effect during the O3 participated coagulation improves the performance of dual-membrane process - Lei Xu; Shian Song; Nigel J.D. Graham; Wenzheng Yu (Chemical Engineering Journal, 2023)

Hydrolyzed polyacrylonitrile UF-membrane for surface and TAP water treatment: Influence on DBPs formation and removal - Muhammad Saboor Siddique; Qingyun Song; Xuejun Xiong; Hasan Fareed; Nigel Graham; Wenzheng Yu (Chemical Engineering Journal, 2023)

Double positively charged polyamide nanofiltration membrane with PEI/Zr4+ for Cr3+ and trimethoprim removal - Jinqiang Wang; Zhaoyang Su; Nigel J.D. Graham; Hongkai Liu; Kai Sun; Wenzheng Yu (Chemical Engineering Journal, 2023)

Bubbleless aerated-biological activated carbon as a superior process for drinking water treatment in rural areas - Mengjie Liu; Nigel Graham; Lei Xu; Kai Zhang; Wenzheng Yu (Water Research, 2023)

Protein-folding-inspired approach for UF fouling mitigation using elevated membrane cleaning temperature and residual hydrophobic-modified flocculant after flocculation-sedimentation pre-treatment - Zhangzheng Wang; Ruhui Chen; Yunyun Li; Weiben Yang; Ziqi Tian; Nigel J.D. Graham; Zhen Yang (Water Research, 2023)

Exploring impacts of water-extractable organic matter on pre-ozonation followed by nanofiltration process: Insights from pH variations on DBPs formation - Muhammad Saboor Siddique; Hongbo Lu; Xuejun Xiong; Hasan Fareed; Nigel Graham; Wenzheng Yu (Science of The Total Environment, 2023)

Enhanced removal of trace pesticides and alleviation of membrane fouling using hydrophobic-modified inorganic-organic hybrid flocculants in the flocculation-sedimentation-ultrafiltration process for surface water treatment - Yunyun Li; Yadong Wang; Jin Jin; Ziqi Tian; Weiben Yang; Nigel J.D. Graham; Zhen Yang (Water Research, 2023)

Statistical analysis of preclinical inter-species concordance of histopathological findings in the eTOX database - Peter S.R. Wright; Katharine A. Briggs; Robert Thomas; Graham F. Smith; Gareth Maglennon; Paulius Mikulskis; Melissa Chapman; Nigel Greene; Benjamin U. Phillips; Andreas Bender (Regulatory Toxicology and Pharmacology, 2023)

Retrospective analysis of the potential use of virtual control groups in preclinical toxicity assessment using the eTOX database - Peter S.R. Wright; Graham F. Smith; Katharine A. Briggs; Robert Thomas; Gareth Maglennon; Paulius Mikulskis; Melissa Chapman; Nigel Greene; Benjamin U. Phillips; Andreas Bender (Regulatory Toxicology and Pharmacology, 2023)

Efficient electrochemical generation of active chlorine to mediate urea and ammonia oxidation in a hierarchically porous-Ru/RuO2-based flow reactor - Kai Zhang; Yuanxiao Duan; Nigel Graham; Wenzheng Yu (Journal of Hazardous Materials, 2023)

Ultra-low concentrations of detection for fluoride and trivalent chromium ions by multiple biomimetic nanochannels in a PET membrane - Jinqiang Wang; Nigel Graham; Kai Sun; Liping Wen; Wenzheng Yu (Journal of Cleaner Production, 2023)

Engineering of 3D graphene hydrogel-supported MnO2–FeOOH nanoparticles with synergistic effect of oxidation and adsorption toward highly efficient removal of arsenic - Kai Zhang; Fengchen Guo; Nigel Graham; Wenzheng Yu (Environmental Pollution, 2023)

Insights into the properties of surface waters and their associated nanofiltration membrane fouling: The importance of biopolymers and high molecular weight humics - Long Tian; Peng Zhou; Zhaoyang Su; Ting Liu; Nigel Graham; Tom Bond; Wenzheng Yu (Chemical Engineering Journal, 2023)

Intradialytic cycling does not exacerbate microparticles or circulating markers of systemic inflammation in haemodialysis patients - Patrick J. Highton; Daniel S. March; Darren R. Churchward; Charlotte E. Grantham; Hannah M. L. Young; Matthew P. M. Graham-Brown; Seila Estruel; Naomi Martin; Nigel J. Brunskill; Alice C. Smith; James O. Burton; Nicolette C. Bishop (European Journal of Applied Physiology, 2022)
Purpose Patients receiving haemodialysis (HD) display elevated circulating microparticle (MP) concentration, tissue factor (TF) expression and markers of systemic inflammation, though regular intradialytic cycling (IDC) may have a therapeutic effect. This study investigated the impact of regular, moderate-intensity IDC on circulating MPs and inflammatory markers in unit-based HD patients. Methods Patients were cluster-randomised to intervention ( n = 20, age: 51.4 ± 18.1 years, body mass: 77.6 ± 18.3 kg, mean ± SD) or no-exercise control ( n = 20, 56.8 ± 14.0 years, 80.5 ± 26.5 kg). Intervention participants completed 30 min of moderate intensity (rating of perceived exertion [RPE] of 12–14) IDC, thrice weekly for 6 months. Pre-dialysis venous blood samples were obtained at 0, 3 and 6 months. Circulating MP phenotypes, cytokines, chemokine and MP TF expression were quantified using flow cytometry and cytometric bead array assays. Results Despite high exercise compliance (82%), no IDC-dependent effects were observed for any MP, cytokine or chemokine measure ( p ≥ 0.051, η ρ 2 ≤ 0.399) other than TNF-α ( p = 0.001, η ρ 2 = 0.186), though no significance was revealed upon post hoc analysis. Conclusion Six months of regular, moderate-intensity IDC had no effect on MPs, cytokines or chemokines. This suggests that the exercise did not exacerbate thrombotic or inflammatory status, though further functional assays are required to confirm this. Trial registration ISRCTN1129707, prospectively registered on 05/03/2015.

A review of a decade of lessons from one of the world’s largest MPAs: conservation gains and key challenges - Graeme C. Hays; Heather J. Koldewey; Samantha Andrzejaczek; Martin J. Attrill; Shanta Barley; Daniel T. I. Bayley; Cassandra E. Benkwitt; Barbara Block; Robert J. Schallert; Aaron B. Carlisle; Pete Carr; Taylor K. Chapple; et al. (Marine Biology, 2020)

Future Research Directions on the “Elusive” White Shark - Charlie Huveneers; Kirin Apps; Edgar E. Becerril-García; Barry Bruce; Paul A. Butcher; Aaron B. Carlisle; Taylor K. Chapple; Heather M. Christiansen; Geremy Cliff; Tobey H. Curtis; Toby S. Daly-Engel; Heidi Dewar; et al. (Frontiers in Marine Science, 2018)

Measuring ecological niche overlap from occurrence and spatial environmental data - Olivier Broennimann; Matthew C. Fitzpatrick; Peter B. Pearman; Blaise Petitpierre; Loïc Pellissier; Nigel G. Yoccoz; Wilfried Thuiller; Marie‐Josée Fortin; Christophe Randin; Niklaus E. Zimmermann; Catherine H. Graham; Antoine Guisan (Global Ecology and Biogeography, 2012)
Aim Concerns over how global change will influence species distributions, in conjunction with increased emphasis on understanding niche dynamics in evolutionary and community contexts, highlight the growing need for robust methods to quantify niche differences between or within taxa. We propose a statistical framework to describe and compare environmental niches from occurrence and spatial environmental data. Location Europe, North America and South America. Methods The framework applies kernel smoothers to densities of species occurrence in gridded environmental space to calculate metrics of niche overlap and test hypotheses regarding niche conservatism. We use this framework and simulated species with pre‐defined distributions and amounts of niche overlap to evaluate several ordination and species distribution modelling techniques for quantifying niche overlap. We illustrate the approach with data on two well‐studied invasive species. Results We show that niche overlap can be accurately detected with the framework when variables driving the distributions are known. The method is robust to known and previously undocumented biases related to the dependence of species occurrences on the frequency of environmental conditions that occur across geographical space. The use of a kernel smoother makes the process of moving from geographical space to multivariate environmental space independent of both sampling effort and arbitrary choice of resolution in environmental space. However, the use of ordination and species distribution model techniques for selecting, combining and weighting variables on which niche overlap is calculated provide contrasting results. Main conclusions The framework meets the increasing need for robust methods to quantify niche differences. It is appropriate for studying niche differences between species, subspecies or intra‐specific lineages that differ in their geographical distributions. Alternatively, it can be used to measure the degree to which the environmental niche of a species or intra‐specific lineage has changed over time.

Cohorts and consortia conference: a summary report (Banff, Canada, June 17–19, 2009) - Paolo Boffetta; Graham A. Colditz; John D. Potter; Laurence Kolonel; Paula J. Robson; Reza Malekzadeh; Daniela Seminara; Ellen L. Goode; Keun-Young Yoo; Paul Demers; Richard Gallagher; Ross Prentice; et al. (Cancer Causes & Control, 2011)

Do S-type granites commonly sample infracrustal sources? New results from an integrated O, U–Pb and Hf isotope study of zircon - Sarah K. Appleby; Martin R. Gillespie; Colin M. Graham; Richard W. Hinton; Grahame J. H. Oliver; Nigel M. Kelly (Contributions to Mineralogy and Petrology, 2010)

Ferrate(VI) enhanced photocatalytic oxidation of pollutants in aqueous TiO2 suspensions - Virender K. Sharma; Nigel J. D. Graham; Xiang-Zhong Li; Bao-Ling Yuan (Environmental Science and Pollution Research, 2010)

Plant–pollinator interactions in a Mexican Acacia community - Nigel E. Raine; Alice Sharp Pierson; Graham N. Stone (Arthropod-Plant Interactions, 2007)

Visual fields in Flamingos: chick-feeding versus filter-feeding - Graham R. Martin; Nigel Jarrett; Phillip Tovey; Craig R. White (The Science of Nature, 2005)

Pathogenicity of bacterium, Xenorhabdus nematophila isolated from entomopathogenic nematode (Steinernema carpocapsae) and its secretion against Galleria mellonella larvae - Ali Nawaz Mahar; Muhammad Munir; Sami Elawad; Simon Richard Gowen; Nigel Graham Meckenzi Hague (Journal of Zhejiang University-SCIENCE B, 2005)